VET practitioner's perceptions of VET higher-education qualifications. (2nd January 2017) - Redmond, Petrea
Abstract: The quality of vocation education and training (VET) teaching in Australia has long been contested. Six Australian universities jointly conducted an online survey exploring the experiences of practitioners who were undertaking undergraduate studies in VET. This paper explores the experiences of VET practitioners as students in one regional university who were enrolled in a Bachelor of Vocational Educational and Training and compared them to the larger national cohort. While the background and capabilities of these practitioners differed in numerous ways there were similarities in their perceptions of what constitutes quality VET teacher education and the knowledge and skills they gained from studying a Bachelor-level qualification when compared to the Certificate IV in Training and Assessment.